The importance of developing critical and creative thinking skills through reading exercises in 7th grade students. Proposal: Creating a booklet with A1-level reading exercises to promote 7th graders’ critical and creative thinking skills. - Pinos Alvia, Melannie Ruth (2024)
PDF